Efeitos do represamento sobre a estrutura e dinâmica da comunidade zooplanctônica. - Takahashi, Erica Mayumi (Universidade Estadual de Maringá. Departamento de Biologia. Programa de Pós-Graduação em Ecologia de Ambientes Aquáticos Continentais., 2008)
The river impoundment for reservoir creation is considered an anthropogenic activity of vast impact for biological communities. The present study was elaborated in two chapters and aimed to obtain greater information about the alterations in the structure and dynamics of zooplankton community during the reservoirs filling, since the ecological importance of this community in reservoirs and due to the scarcity of information about these changes in this community. The first chapter was elaborated from data obtained in one subtropical reservoir (Santa Clara reservoir, Jordão river, Paraná State) and predicted that: (i) the species richness and specific diversity of zooplankton groups are higher in the beginning of the filling phase, due to the presence of non planktonic species; (ii) the abundance of the groups is greater in the end of the same phase, in function of the development and predominance of large planktonic populations due to the food resources availability and the reduction of current flow and (iii) the alterations in the species richness, abundance, specific diversity are more remarkable in the beginning of the reservoir filling, due to the changes in the physical, chemical and biological features of the water. We identified 108 rotifer species, 32 cladoceran species and 16 copepod species. There was an increasing trend in the species richness of all groups during the filling, and the higher values were observed at the end of the period. Rotifers compounded the group with the highest alteration in species composition, followed by cladocerans and copepods. Greater abundances of all groups were registered at the end of the study period, but the peak of abundance of rotifers was higher and previous than those recorded for cladocerans and copepods (cyclopoids and calanoids). In general, the variations in the values of specific diversity were clear to all zooplankton groups and were mainly related to evenness results. As also observed for specific diversity, the evenness values of all groups presented ...